Intracranial extramedullary haematopoiesis: A case report. (3rd September 2015) - Mehta, Samir; Shapey, Jonathan; Pohl, Ute; Vindlacheruvu, Raghu
Abstract : Extramedullary haematopoiesis (EMH) is an ectopic production of blood cells to compensate for ineffective haematopoiesis. We report a rare symptomatic presentation of intracranial EMH and discuss its investigation and management. EMH should be considered a differential diagnosis in patients with haemoglobinopathies, haemolytic anaemias and myeloproliferative disorders, who present with symptoms of raised intracranial pressure.